Enhanced Angular Resolution in OEST Radar Using Hybrid APES-MUSIC Algorithm - RANDI RAMDANSYAH; SYAHFRIZAL TAHCFULLOH; DWI RISKY; NUR SAFARIA; ILHAM TIARA PUTRA (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
Limited angular resolution in Overlapped Equal Subarray Transmit (OEST) radar poses a critical challenge in detecting closely spaced targets, especially in complex multi-target environments. This paper evaluates super-resolution MUSIC and APES methods to enhance angular resolution in OEST radar systems with 6 subarrays. Performance analysis was conducted under single and multiple target scenarios: one target at 0.5°, two targets at [0°, 0.5°], and three targets at [–0.5°, 0°, 0.5°]. Both methods achieved accurate angle detection for single and dual-target cases. However, in triple-target scenarios, APES demonstrated superior DoA and RCS estimation precision (up to 0.999) despite higher sidelobes, whereas MUSIC showed reduced RCS accuracy but lower sidelobes. The hybrid APES-MUSIC approach produced sharp spectral peaks, near-unity amplitude response, and minimized sidelobe interference, significantly improving estimation accuracy and stability for this radar in dense multi-target settings.